MULTIKULTURALISME DALAM PENDIDIKAN ANAK USIA DINI - Puspita, Widya Ayu (JIV-Jurnal Ilmiah Visi, 2013)
In the pluralistic society, the insight of multiculturalism is essential in creating peaceful life of the society. This article discusses how education plays in building mutlicultural character among the society members. If the children learn and understand multiculturalism at their early age, they will be tolerant of the differences. Having reviewing the existing literature critically, this article concludes that the institution of early childhood education has a strategic role in multicultural education. The early childhood education institution should design and develop multicultural learning environment in growing their appriciation of multiculturalism. The teachers are encouraged to work together with the parents, society members, and nongoverment organizations to meet the multicultural needs of the children.